Hepatic stellate cell senescence in liver fibrosis: Characteristics, mechanisms and perspectives. (October 2021) - Zhang, Mengfan; Serna-Salas, Sandra; Damba, Turtushikh; Borghesan, Michaela; Demaria, Marco; Moshage, Han
Highlights: This review discusses the basic mechanism of cell senescence, in particular hepatic stellate cells. The role of hepatic stellate cell senescence in liver fibrosis is discussed in detail. Discussion of the potential of inducing stellate cell senescence for therapeutic intervention. Abstract: Myofibroblasts play an important role in fibrogenesis. Hepatic stellate cells are the main precursors of myofibroblasts. Cellular senescence is the terminal cell fate in which proliferating cells undergo irreversible cell cycle arrest. Senescent hepatic stellate cells were identified in liver fibrosis. Senescent hepatic stellate cells display decreased collagen production and proliferation. Therefore, induction of senescence could be a protective mechanism against progression of liver fibrosis and the concept of therapy-induced senescence has been proposed to treat liver fibrosis. In this review, characteristics of senescent hepatic stellate cells and the essential signaling pathways involved in senescence are reviewed. Furthermore, the potential impact of senescent hepatic stellate cells on other liver cell types are discussed. Senescent cells are cleared by the immune system. The persistence of senescent cells can remodel the microenvironment and interact with inflammatory cells to induce aging-related dysfunction. Therefore, senolytics, a class of compounds that selectively induce death of senescent cells, were introduced as treatment to remove senescent cells and consequently decrease the disadvantageous effects of persisting senescent cells. The effects of senescent hepatic stellate cells in liver fibrosis need further investigation.